New anatomical form of occlusal surface on permanent maxillary first molars (2014)
Introduction: an undefined sulcus on the permanent maxillary first molars (PMFM) allowed the identification of two types of occlusal surfaces: that described by Figún and Garino, Type 1 for the research group, and Type 2, characterized by the presence of a sulcus above the oblique ridge, that runs along it without breaking it. This observation allowed studies to be undertaken in order to determine its presence and investigate its origin, direction and length, to characterize it and register it as a new form of occlusal surface. Methods: we worked with natural PMFM, both inert and in patients, to demonstrate the presence of the sulcus and the PMFM that present the groove in order to characterize it. The method was observational and descriptive. Results: there is a predominance of cases in which the occlusal surface of the PMFM presents a sulcus that partially runs along the oblique ridge, without breaking it. It begins in the main central triangular fossa and runs towards the distal and palatal, its length varying between 1 and 2 mm. These results have allowed this occlusal surface to be registered as Type II PMFM. Conclusion: the PMFM presents two types of occlusal surface: Type I and Type II.